Symptom reduction in mal de débarquement syndrome with attenuation of the velocity storage contribution in the central vestibular pathways - Maruta, Jun; Cho, Catherine; Raphan, Theodore; Yakushin, Sergei B. (Frontiers in Rehabilitation Sciences, 2024)
Background: The velocity storage mechanism of the central vestibular system is closely associated with the vestibulo-ocular reflex (VOR), but also contributes to the sense of orientation in space and the perception of self-motion. We postulate that mal de débarquement syndrome (MdDS) is a consequence of inappropriate sensory adaptation of velocity storage. The premise that a maladapted velocity storage may be corrected by spatial readaptation of the VOR has recently been translated into the development of the first effective treatment for MdDS. However, this treatment’s initial impact may be reversed by subsequent re-triggering events. Presently, we hypothesized that MdDS symptoms could alternatively be reduced by attenuating the velocity storage contribution in the central vestibular pathways. Methods: Forty-three patients with MdDS (aged 47±14 yo; 36 women) were randomly assigned to two treatment groups and followed for 6 months. The horizontal VOR was tested with chair rotation during laboratory visits, and the strength of velocity storage was quantified with model-based parameters—the time constant (Tc) and the gain of coupling from the vestibular primary afferent signals (g0). To attenuate velocity storage, Group 1 underwent a progressively intensifying series of low-frequency earth-vertical oscillatory rotation coupled to conflicting visual stimuli. Group 2 underwent an established protocol combining head tilts and visual stimulation, designed to correct maladapted spatial orientation but not change the velocity storage strength. The symptom severity was self-rated on an 11-point scale and reported before and up to 6 months after the treatment. Results: In Group 1, velocity storage was modified through reduction of g0 (p < 0.001) but not Tc. The symptom rating was at least halved initially in 43% of Group 1 (p = 0.04), the majority of whom retained a similar level of improvement during the 6-month follow-up period. In Group 2, no systematic change was induced in the parameters of velocity storage strength, as expected. The symptom rating was at least halved initially in 80% of Group 2 (p < 0.001), but paralleling previous findings, symptoms often returned subsequently. Conclusion: Attenuation of velocity storage shows promise as a lasting remedy for MdDS that can complement the VOR readaptation approach.